Advancing Global Competence in Higher Education through Education for Sustainable Development (ESD) (Journal of Informatics Education and Research, 2026)
In the world becoming very globalized and the global matters becoming more complicated than ever, institutions of higher learning should prepare students with effective global competencies. Global competence encompasses global awareness, intercultural understanding, moral responsibility, and critical thought, and thus is one the main educational focus. The Education Sustainable Development (ESD) has proven to be a useful educational model that is similar in aspiration to the developmental competence of the globe. Teaching with the help of ESD makes students see the global sustainability problems in different perspectives and perceive the interrelation of the environmental, social, and economic dimensions of development. The current paper discusses the role of Education for Sustainable Development in promoting global competence in higher education. The research applies conceptual and secondary data based study research methodology that depends on the literature, global frameworks, and policy documents of such organizations as UNESCO (United Nations Educational, Scientific and Cultural Organization) and OECD (Organization for Economic Co-operation and Development). The paper follows a systematic review of the literature addressing the relationship between ESD and global competence and ways in which higher education institutions can incorporate ESD into their curriculums, teaching experience, policies, and campus life. The paper further highlights the significance of universities in facilitating practical learning, the interdisciplinary approach, and international collaborations to enhance the involvement and learning outcomes of students. Nevertheless, implementation of ESD in higher education is hindered by several challenges which include rigid curricula, staff preparation, resources and problems with measuring the outcomes of global competence. The paper has concluded that the successful implementation of ESD can only be done through an increased institutional commitment, an improved faculty development, and the use of new assessment methods. On balance, the paper emphasizes the fact that Education for Sustainable Development is an efficient way to prepare graduates that can respond to contemporary global issues and contribute to the establishment of a sustainable, inclusive future.